Turning small business interns into applicants: The mediating role of perceived justice - Zhao, Hao (Journal of Business Venturing, 2013)
Internship is a relatively low-risk approach for entrepreneurs to attract and select prospective employees. But what factors can influence interns' intentions to join small businesses? Based on the model of action phases, realistic job preview theory, and organizational justice theory, I hypothesize that interns' post-internship intentions to join can be predicted by their pre-internship job-seeking goal and their during-internship involvement with the host organization. Perceived organizational justice is hypothesized to mediate the relationship between involvement and post-internship intentions to join. Temporally lagged data from 104 small business interns support most hypotheses. In addition, compared to a group of 175 corporate interns, small business interns are more likely to change their minds after the internship, and justice perception has a stronger effect on their post-internship intentions to join.